Literatura e consciência - Ianni, Octavio (Revista do Instituto de Estudos Brasileiros, 1988)
The brazilian literary production about the Blacks permits us alresdy to speak of a black literature. If we look at the brazilian literature on a general view of the whole, we will see that a section is detached and turning independent. It forms a system of works, authors and readers, articulated round a serie of problems, a imaginated populated by constructions, images, figures, reverberating the drama and the epos of brazilian epos of the brazilian Blacks. In human, social and cultural terms, the negro constitutes a nucleous sufficiently distinctive, remarkable of the literary production.